The indoor fate of terpenes: Quantification of the limonene uptake by materials. (15th January 2021) - Thevenet, F.; Verriele, M.; Harb, P.; Thlaijeh, S.; Brun, R.; Nicolas, M.; Angulo-Milhem, S.
Abstract: Beyond their indoor emission by various sources, another aspect of the presence of VOCs in confined environments involves their indoor fate. Terpenes, because of their ubiquity, source variety and reactivity, are VOCs whose contributions to the indoor air quality may largely exceed primary emissions because of possible secondary processes such uptake and secondary emissions. Limonene is flagged as a species typifying the behavior of terpenes, and a selection of representative indoor materials is proposed. Limonene uptake characterization of selected surfaces is performed under typical indoor conditions using a FLEC-based experimental setup allowing (i) limonene partitioning coefficient determination and (ii) quantification of the reversible nature of this interaction. Interestingly, the materials of interest exhibit highly differentiated affinities for limonene, evidencing the contrast in their surface contributions to terpene loss. Glazing is confirmed as a non-significant sink, while cotton fabric and gypsum board are major contributors to limonene surface loss and exhibit high surface uptake capacities. This work allows a quantitative ranking of the selected materials from minor to major limonene sinks. Reversibility quantification of the uptake process provides key insights into further secondary limonene emissions. The major sink materials are highlighted such as inducing irreversible limonene uptake, thus creating indoor surface pools of reactive organics possibly available for further oxidation processes. Graphical abstract: Image 1 Highlights: Effective and reliable methodology for partitioning coefficient (K) determination. Characterization of the reversibility of limonene uptake onto building materials. Quantitative ranking of real building materials regarding limonene uptake. Evidence for building material behavior as sinks and/or secondary sources of terpenes.